2008
DOI: 10.1063/1.2904862
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the room temperature magnetism of ZnO∕Co3O4 mixtures

Abstract: The origin of room temperature ferromagnetic like behavior (RT-FM) in ZnO-based diluted magnetic semiconductors (DMS) is still an unclear question. The present work concentrates on the appearance of Room temperature magnetic moments in just mixed ZnO/Co 3 O 4 mixtures without thermal treatment. In this study is shown that the magnetism seems to be related to surface reduction of the Co 3 O 4 nanoparticles. In which, an antiferromagnetic Co 3 O 4 nanoparticle (core) is surrounded by CoO-like shell. This sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 14 publications
4
33
0
1
Order By: Relevance
“…1 In the last years, research has been focused mainly on oxides doped with magnetic ions ͑the so-called diluted magnetic semiconductors͒. Recent results [2][3][4][5] indicate that the appearance of magnetism in these oxides ͑mainly ZnO and TiO 2 ͒ is related to the presence of defects and surface/interface effects 6,7 but the origin of most of the experimental results is still unclear. 8 Actually, results are hardly reproducible and findings from different groups are commonly contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the last years, research has been focused mainly on oxides doped with magnetic ions ͑the so-called diluted magnetic semiconductors͒. Recent results [2][3][4][5] indicate that the appearance of magnetism in these oxides ͑mainly ZnO and TiO 2 ͒ is related to the presence of defects and surface/interface effects 6,7 but the origin of most of the experimental results is still unclear. 8 Actually, results are hardly reproducible and findings from different groups are commonly contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we refer to the investigations where it was found that interfaces between Co 3 O 4 and ZnO are involved in the observed FM in (Zn, Co)O systems [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Here, the FM seems to be related to the surface reduction of the Co 3 O 4 nanoparticles that are surrounded by the CoO-like shell [38]. Based on these results, we could assume that the observed FM in our Zn 1−x Co x O (x = 0 01, 0 03) powders can be ascribed to the formation of interfaces between two dissimilar valence ions i.e., Co 3+ ions from Co 3 ions is responsible for the observed FM via a possible double-exchange mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Complex oxides of cobalt find applications in gas sensing, [88,89] spintronics, [90][91][92][93] batteries, [89,91] and catalysis [94][95][96][97][98][99][100][101], most notably for oxidation of carbon monoxide (CO) [96,97] and water. [98][99][100][101] At room temperature, the most † Contributions: KJK designed and performed the experiments related to the sample growth, RHEED, AFM, XRD, and XPS and analyzed the data.…”
Section: Introductionmentioning
confidence: 99%